FACTORS THAT PROMOTING MARINE ECOTOURISM IN THE EASTERN ECONOMIC CORRIDOR (EEC) A CASE STUDY OF PATTAYA - ดีจริงตระกูล, ปุณณ์ณฤณัฏฐ์ (Academic Journal Phranakhon Rajabhat University, 2019)
This research aimed to study of tourism management factors that can promoting sustainable marine ecotourism in Pattaya city of the Eastern Economic Corridor (EEC). The researcher used a qualitative research model by using 400 questionnaires of both Thai and foreign tourists who come to visit Pattaya city on Saturday – Sunday and beginning of the month to collected opinions on sustainable marine ecotourism. The researcher used statistical analysis such as percentage, mean, Independent sample t-test, One-Way ANOVA F-test and Multiple Regression Analysis (MRA). The results showed that the difference of Gender, age, education level, occupation, income and number of marine tourism trips have diference average level of sustainability of marine ecotourism which increasing benefits and reducing negative impacts to socially and economically, culture and environment at statistically significant of 0.05. While tourism management factors that promoting sustainable marine ecotourism in the Eastern Economic Corridor area at significant of 0.05 consist of 1) Social and economic aspects for the local community as an attractions factor with the F = 2.718 Sig. = 0.020 and the decision coefficient (R Square) is 0.33. 2) Cultural aspects for communities and tourists as and accessibility factor with the F = 7.274 Sig. = 0.000 and the decision coefficient (R Square) is 0.085 and 3) Environmental factors as an activities factor with the F = 7.623 Sig. = 0.000 and the decision coefficient (R Square) is 0.88.